Improving wear resistance of responsible hydraulic hammer details with ion-plasma treatment - Glushkova, D. B.; Ryzhkov, Yu. V.; Kostina, L. L.; Chigrin, A. A.; Stepanyuk, A. I.; Глушкова, Д. Б.; Рижков, Ю. В.; Костіна, Л. Л.; Чигрин, А. О.; Степанюк, А. І.; Глушкова, Д. Б.; Рыжков, Ю. В.; et al. (Харківський національний автомобільно-дорожній університет, 2020)
Details of the hammer during operation are subject to wear, which leads to a decrease in their service life. In accordance with the literature data in the practice of engineering uses many methods of hardening, which do not give a significant effect. Therefore, the application of new methods of surface hardening has become topical. These methods include ion-plasma chromium plating. On the basis of experimental studies, the effect of ion-plasma chromium plating on the wear resistance and mechanical properties of hydraulic hammer parts has been established, structural changes in the material have been analyzed. Ion-plasma chromizing of the parts pro-motes the increase of their wear resistance in 1.75 times as compared to those which are not strengthened. The technology of ion-plasma chromizing secures the running of the strengthened parts without breaking off and chipping. The zones of structural changes are marked on the sec-tions of parts damages, which are typical for the effects of the second hardening.
Підвищення зносостійкості відповідальних деталей гідромолота іонно-плазмовим обробленням
Повышение износостойкости ответственных деталей гидромолота ионно-плазменной обработкой
Keywords: ion-plasma chromium plating; hydraulic hammer; wear resistance; іонно-плазмове хромування; гідромолот; опір зношуванню; ионно-плазменное хромирование; гидромолот; сопротивление износу; 669.017; 10.30977/BUL.2219-5548.2020.88.1.7